2016
DOI: 10.1055/s-0035-1562438
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of d-Fagomine and Its Seven- and Eight-Membered Higher-Ring Analogues, and the Formal Synthesis of (+)-Australine from l-Xylose-Derived Chiron

Abstract: ‡ These authors contributed equally to this work. H N HO HO OH D-fagomine HN HO HO OH HN HO HO OH N HO HO OH OH (+)-australine BnO OBn OH BnO L-xylose O HO OH OH HO AbstractThe synthesis of D-fagomine and its seven-and eight-membered higher-ring analogues from commercially available L-xylose is reported. The syntheses involve elaboration of a common alkenol precursor obtained from L-xylose-derived hemiacetal. The key steps in the syntheses are intramolecular reductive amination and ring-closing metathesis for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…[α] D 20 = +11.8 ( c = 1.50, CHCl 3 ). 1 H and 13 C NMR spectra of compound (4 S )- 4 are in accordance with literature data …”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…[α] D 20 = +11.8 ( c = 1.50, CHCl 3 ). 1 H and 13 C NMR spectra of compound (4 S )- 4 are in accordance with literature data …”
Section: Methodssupporting
confidence: 87%
“…1 H and 13 C NMR spectra of compound (4S)-3 are in accordance with literature data. 25 2-((1R,2S,3S)-2,3-Dibenzyloxy-1-(benzyloxymethyl)pent-4-enyl)isoindoline-1,3-dione ((4R)-3). From alcohol (4S)-2 (532 mg, 1.27 mmol) following the general procedure for Mitsunobu reaction, the product (4R)-3 (488 mg, 70%) was isolated as a colorless viscous oil.…”
Section: -((1s2s3s)-23-dibenzyloxy-1-(benzyloxymethyl)pent-4-enyl)iso...mentioning
confidence: 99%
“…In recent decades, many efficient sulfa-Michael additions have been widely reported using thiols as nucleophiles to attack various Michael acceptors. 1–4 By summarizing these works, we found that the published approaches could be divided into four different pathways: transition metal catalysis, 1 organocatalysis, 2 green chemistry methods, 3 and heterogeneous catalysis. 4 However, most methods focused on adding thiols to di-substituted Michael acceptors, constructing tertiary centers.…”
Section: Introductionmentioning
confidence: 99%